2020
DOI: 10.1177/0033294120980967
|View full text |Cite
|
Sign up to set email alerts
|

Υoung Adults’ Assertiveness in Relation to Parental Acceptance-Rejection in Greece and in Bosnia and Herzegovina

Abstract: This study explored the relation between assertiveness and parental behavior as perceived by young adults through parental acceptance-rejection and behavioral and psychological control. Αssertiveness is a mode of personal behavior and communication characterized by willingness to stand up for one’s own needs and interests in an open and direct way. Inappropriate parenting may be associated with assertiveness difficulties and as evidence-based findings from many surveys have shown that assertive skills can be i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 57 publications
(67 reference statements)
1
0
0
Order By: Relevance
“…This is consistent with past findings which found that IPP were linked with a sense of parental rejection, lowering their mental health [32,34,61]. The findings of the present research provide support for the IPARTheory, which postulates that perceived parental acceptance-rejection plays a major role in the emotional, behavioral, cognitive, and social development in children [9,[62][63][64][65]. As explained by Rohner [5], this is because humans have a need for positive response, including an emotional desire for comfort, care, and love (otherwise known as parental acceptance).…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with past findings which found that IPP were linked with a sense of parental rejection, lowering their mental health [32,34,61]. The findings of the present research provide support for the IPARTheory, which postulates that perceived parental acceptance-rejection plays a major role in the emotional, behavioral, cognitive, and social development in children [9,[62][63][64][65]. As explained by Rohner [5], this is because humans have a need for positive response, including an emotional desire for comfort, care, and love (otherwise known as parental acceptance).…”
Section: Discussionsupporting
confidence: 92%